Pengaruh Konsentrasi Sukrosa Terhadap Karakteristik Wine Kopi Arabika Kintamani - Andriana Sastrawan, I Putu; Duniaji, Agus Selamet; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i03.p07, 2022)
This research was conducted to determine the effect of sucrose concentration on characteristic of kintamani arabica coffee wine and to determine concentration of sucrose that produced the best characteristic. The research used a Randomized Block Design with faktor of sucrose concentration that concists of 5 levels (10% ,15%, 20%, 25%, 30% ) Each treatment was repeated 3 times resulting 15 experimental units. The data were analyzed by Analysis Of Variance and the treatment show effect is observed by Duncan Multiple Range Test (DMRT). The results showed that sucrose concentration had significant effect to total Soluble solids (TSS), pH, total acid, etanol content, hedonik of taste, score of taste and overall acceptance. The concentration of 25% sucrose produced the best characteristic of Kintamani arabica coffe wine with total disollved solids 17,20 0Brix, pH 3.95, total acid 0.15%, etanol content 9,58 %, was liked color (5.53), slightly liked aroma (5.27), slightly liked flavor (5.40), sweet flavor (3.13), slightly sour flavor (2.00), slightly bitter flavor (1.73 ) and the overall acceptance is rather liked (5,20).